Examining the influence of distal radius orientation on distal radioulnar joint contact using a finite element model. (3rd February 2016) - Greybe, Desney; Boland, Michael R.; Wu, Tim; Mithraratne, Kumar
Summary: Distal radius malunion is a problem that is common to distal radius fractures and can affect the contact mechanics of the distal radioulnar joint (DRUJ). The goal of this study was to use a computational model of the DRUJ to investigate the influence distal radius orientation has on its contact mechanics. Detailed, finite element models of the radius and ulna bones were constructed from magnetic resonance imaging data. The orientation of the distal radius was rotated in 2° increments about three orthogonal axes representing dorsal–palmar rotation, radial–ulnar rotation and anteversion‐retroversion. A computational model was used to predict joint contact at the DRUJ in each condition. Joint contact was found to be most sensitive to dorsal rotation of the distal radius, while radial and ulnar rotation did not substantially affect joint contact pressure. Slight retroversion was found to lower joint contact pressure. In most cases, more than 6° rotation in a given direction resulted in dislocation of the DRUJ, so that adaptation at the joint would be required to maintain articular contact. The joint contact model implemented in this study allowed the relationship between distal radius orientation and DRUJ contact to be examined systematically, in a way that is difficult to achieve using a cadaver‐based approach. The results demonstrated the distal radius displacements most critical for maintaining healthy joint mechanics at the DRUJ. It is important that clinicians consider the influence of distal radius malunion and its treatment on DRUJ mechanics, in addition to its consequences for wrist function and forearm rotation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Distal radius malunion is a common and debilitating disorder. In this paper, a finite element model was used to study the influence of distal radius orientation on distal radioulnar joint mechanics. Joint contact was most sensitive to dorsal rotation and anteversion of the distal radius. In most cases, more than 6° rotation would necessitate adaptation to maintain articular contact. This study represents an important step towards properly understanding distal radius malunion, as it relates to distal radioulnar joint mechanics.